Conservation status of tree species in Himchari National Park of Cox's Bazar, Bangladesh (Journal of Biodiversity Conservation and Bioresource Management, 2018)
Himchari National Park (HNP) was declared as a Protected Area (PA) in 1980 under the section 23(II) of Bangladesh Wildlife Preservation Act 1974 of the Government of the People’s Republic of Bangladesh. The total area of the HNP is about 1,729 ha (4,271.15 acres) under the jurisdiction of Cox’s Bazar South Forest Division, Cox’s Bazar district. Once the forest was very rich in flora and fauna, but many of the species have disappeared due to habitat destruction, over-exploitation, habitat fragmentation, fire hazard, encroachment, indiscriminate harvesting of tree species and Non-Timber Forest products. The study was conducted through extensive whole area survey and quadrat survey methods. A total of 117 tree species (having ≥ 5 cm dbh) belonging to 37 families was recorded from the HNP. Moraceae family possesses the highest species (14) followed by Mimosaceae (8), Euphorbiaceae (7), Myrtaceae (6) and 5 species each by Anacardiaceae, Caesalpiniaceae, Meliaceae and Verbenaceae. A total of 69 tree species (59%) was found as Least Concern (LC) representing maximum tree species among all the categories. Vulnerable, Endangered, Near Threatened and Critically Endangered tree species were represented by 16 species (14%), 4 species (3%), 2 species (2%) and 2 species (2%), respectively. It is necessary to take effective measures for the protection, sustainable management, proper utilization and conservation of tree species in an aim to conserve the forest genetic resources of the Himchari natural forests.J. Biodivers. Conserv. Bioresour. Manag. 2018, 4(2): 1-10